BREAK EVENT POINT ANALYSIS OF STANDARD INPUT COST OF PUBLIC SERVICE AGENCY’S COMPUTER ASSISTED TEST ACTIVITIES (CASE STUDY IN POLYTECHNIC OF XXX YEAR 2019) - Bagas Johantri (Politeknik Negeri Batam, 2020)
This study aims to determine the break event point (BEP) of Computer Assisted Test (CAT) activities in order that the revenue from the CAT is not less than the cost of the implementation. CAT has been proven to increase transparency in employee recruitment. However, for the Public Service Agency (BLU) and the public sector organization that organize the CAT, it is deemed necessary to pay attention to the costs and the revenues from these activities. The question in this research is how to determine the BEP from the standard cost of CAT activities. This is a descriptive qualitative research with a case study. The research uses data collected from the standard input costs for CAT activities. This study separates costs into fixed costs and variable costs. Semivariable costs are separated using the least squares method. The result shows that the total income to reach the BEP is Rp. 55,355,344.37 with at least 222 participants per day. This research shows that cost-volume-profit analysis in cost accounting can be used as an administratorial tool for managing activities in the public sector.